Pencegahan Child Peers Violence melalui Pendidikan Karakter pada Siswa Sekolah Dasar - Indriyany, Ika Arinia; Mayrudin, Yeby Ma'asan; Prastio, Luki Oka; Godjali, Moh Rizky (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Sultan Ageng Tirtayasa, 2025)
This community service was carried out at Seruni 2 Elementary School, Pandeglang Regency, Banten Province with the aim of increasing awareness of elementary school students regarding forms of violence that often occur. Early awareness needs to be increased because violence is often carried out in the guise of jokes. Therefore, the community service team felt the need to conduct socialization regarding the prevention of violence against children. The activities carried out were in the form of story telling guided by resource persons and interspersed with interactive activities in the form of questions and answers. It is hoped that this activity can change the behavior patterns of elementary school students so that they stay away from actions that can be categorized as violence against their peers